Active and passive lower limb flexibility in high level rhythmic gymnastics - Batista Santos, A.; Lemos, M. E.; Lebre, E.; Avila-Carvalho, L (Science of Gymnastics Journal, 2015)
Flexibility is one of the main physical abilities required in Rhythmic Gymnastics practice. It's expected that high level gymnasts as National Teams members show high levels of this motor ability. The aim of this study was to evaluate the level of active and passive flexibility of the lower limbs (preferred and non-preferred) of 5 high level junior gymnasts (13.60 ± 0.25 years old) during a sport season. The limb which effectively performs the task is considered the preferred and the one which functions as support is considered the non-preferred. For the flexibility assessment gymnasts were evaluated performing 7 specific Rhythmic Gymnastics movements in three different moments of the sports season. These movements were filmed and the videos were analyzed. A five point scale (from 0 to 4) was used to classify the performance of the gymnasts in each movement. For statistical analysis nonparametric tests (Mann-Whitney, Friedman and Wilcoxon test) were used. The results revealed that the gymnasts showed a high level of active and passive flexibility for the preferred lower limb (average of 3,98 points in the 7 tests) but lower levels with non-preferred lower limb (average of 3,10 points in the 7 tests). However, the gymnasts registered a significant improvement of the flexibility levels on the non-preferred lower limb at the different measurements moments over the season.